Antibiograms of Bacteria Isolated from Diseased Lungs of Cattle Slaughtered at Abattoir, Ibadan, Nigeria (2022)
This study was undertaken to assess the antimicrobial susceptibility profile of bacterial pathogens isolated from diseased lungs of cattle. Forty-two bacterial isolates obtained from diseased lung tissue samples of cattle slaughtered at Bodija abattoir were tested for antimicrobial susceptibility patterns using the Kirby-Bauer disc diffusion method. The bacteria isolated were Staphylococcus aureus, Streptococcus pneumoniae, Pseudomonas species, Proteus mirabilis, Pasteurella lymphangitidis, Pasteurella multocida, Pasteurella ureae, Pasteurella pneumotropica, Klebsiella pneumoniae, Escherichia coli, Morganella morganii and Mannheimia haemolytica. Selection of antibacterials was on the basis of the Gram reaction of the isolates and each was tested for 10 different antibacterials. A high proportion of the Gram-negative isolates showed sensitivity to ciprofloxacin (75.0 %) and ofloxacin (66.7 %) while a moderate proportion (54.2 %) was sensitive to perfloxacin. A low proportion of the Gram-negative isolates showed sensitivity to amoxicillin/clavulanate (20.0 %), tetracycline (20.8%), amoxicillin (20.8%), trimethoprim (12.5%), sulfamethoxazole (12.5%) and gentamycin (4.2%) while resistance was demonstrated against nitrofurantoin and ceftriaxone. All the isolates of Streptococcus pneumonia were sensitive to cefuroxime, ceftriaxone, ciprofloxacin, streptomycin, trimethoprim/sulfamethoxazole, perfloxacin and chloramphenicol, with very low proportion being sensitive to ampicillin and amoxicillin. Most of the isolates of Staphylococcus aureus were resistant to all the drugs tested. The results of the study showed that the isolates were resistant mostly to the common and relatively cheaper drugs; an important economic impact to the chemotherapeutic management of respiratory disease in cattle.